A Planning Game Over a Map: Playing Cards and Moving Bits to Collaboratively Plan a City - Sousa, Micael (2020)
Rational systemic planning and collaborative planning seem to be two conflicting approaches in spatial planning practice and research. However, some authors are trying to make them compliant through new approaches that are more human centered. Applying games to planning processes can be one of many solutions to consider. This article describes the process of developing an analog game session and the first test of this serious board game approach. This game approach began withmodern board game design elements as a starting design base and was adapted for further developments in game-based planning processes, following the methods of serious games through the adaptation of the design, play, experience framework. The purpose of this game session is to create a simple and flexible tool to train students and future planners for the use of games in the development of collaborative urban planning processes, contributing to filling the gap created by the absence of simple and flexible games to use in daily planning practices.